2008
DOI: 10.1111/j.1471-4159.2008.05652.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and possible role of creatine transporter in the brain and at the blood‐cerebrospinal fluid barrier as a transporting protein of guanidinoacetate, an endogenous convulsant

Abstract: Little is known about the cerebral distribution and clearance of guanidinoacetate (GAA), the accumulation of which induces convulsions. The purpose of the present study was to identify creatine transporter (CRT)‐mediated GAA transport and to clarify its cerebral expression and role in GAA efflux transport at the blood‐cerebrospinal fluid barrier (BCSFB). CRT mediated GAA transport with a Km value of 269 μM/412 μM which was approximately 10‐fold greater than that of CRT for creatine. There was wide and distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 39 publications
4
78
0
Order By: Relevance
“…These observations may explain the absence of Cr in CNS of SLC6A8-deficient patient, despite normal expression of AGAT and GAMT in their brain , as well as the lack of effect of treatment of SLC6A8-deficient patients with arginine as a precursor of Cr (Fons et al 2008). Recent studies also demonstrated the potential role of SLC6A8 (and taurine transporter) for GAA transport across BBB and in brain parenchymal cells (Tachikawa et al 2008(Tachikawa et al , 2009). …”
Section: Creatine In Cns: Endogenous Synthesis Versus Uptake From Permentioning
confidence: 95%
See 2 more Smart Citations
“…These observations may explain the absence of Cr in CNS of SLC6A8-deficient patient, despite normal expression of AGAT and GAMT in their brain , as well as the lack of effect of treatment of SLC6A8-deficient patients with arginine as a precursor of Cr (Fons et al 2008). Recent studies also demonstrated the potential role of SLC6A8 (and taurine transporter) for GAA transport across BBB and in brain parenchymal cells (Tachikawa et al 2008(Tachikawa et al , 2009). …”
Section: Creatine In Cns: Endogenous Synthesis Versus Uptake From Permentioning
confidence: 95%
“…As described above, GAA may appear as a key intermediate player for endogenous Cr synthesis in CNS, as it must most probably be transported from AGAT-to GAMT-expressing cells for Cr synthesis to occur (Braissant et al 2010), just as it does in periphery between AGAT in kidney and GAMT in liver (Edison et al 2007;da Silva et al 2009). It was recently demonstrated that both BBB endothelial cells (Tachikawa et al 2009) and CNS parenchymal cells (Tachikawa et al 2008;Braissant et al 2010) are able to take up GAA by SLC6A8. The Km value of SLC6A8 for GAA appears ten times lower than that for Cr (Tachikawa et al 2008).…”
Section: Creatine and Guanidinoacetate Within Normal Versus Creatine-mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the decrease in total Cr levels observed in our group of athletes with concussive head injury may well be explained by the experimentally documented general depression of brain metabolism after mTBI and corresponding to the window of metabolic brain vulnerability. Since Cr homeostasis in the brain is regulated by exogenous Cr source as well as de novo intracellular synthesis, imbalance in cerebral Cr levels might be caused either by a decreased activity of the Cr transporter 40,42 or by an inhibition of the Cr synthesis. 40,[42][43][44] A further consideration about this intricate matter of the Cr levels following mTBI [26][27][28][29] is given by the preliminary evidence that dietary supplementation of Cr can facilitate recovery of function in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Since Cr homeostasis in the brain is regulated by exogenous Cr source as well as de novo intracellular synthesis, imbalance in cerebral Cr levels might be caused either by a decreased activity of the Cr transporter 40,42 or by an inhibition of the Cr synthesis. 40,[42][43][44] A further consideration about this intricate matter of the Cr levels following mTBI [26][27][28][29] is given by the preliminary evidence that dietary supplementation of Cr can facilitate recovery of function in TBI. [45][46][47] If cerebral Cr levels were induced to increase following mTBI, it is not clear why exogenously administered Cr would enhance recovery after TBI.…”
Section: Discussionmentioning
confidence: 99%